Art and Dialogism: A Bakhtinian Critical Reading of Cláudio Santoro's Nationalist Period (DAPesquisa, 2025)
The article seeks to understand the trajectory and poetics of Cláudio Santoro from the precepts listed by Mikhail Bakhtin, about art.  It evaluates the influence of the composer’s political involvement on his artistic making, during the nationalist period of his work. We adopt as specific methodological bases essays of Bakhtin, in addition to researches of different authorship, such as Formentão (2010), Salgado (2010), Amadio (2015), etc.